The Right to an Effective Remedy - Plavšić, Nataša (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
This paper studies the evolution, scope, and practical significance of Article 13 of the European Convention on Human Rights, which guarantees the right to an effective domestic remedy in cases of alleged violations of Convention rights. Through a systematic analysis of the European Court of Human Rights jurisprudence, the study summaries the development of key concepts for applicability of Article 13 of the ECHR, such as ‘national authority’, ‘arguable claim’, and the criteria that determine whether a remedy is effective in law and in practice. Special attention is given to the relationship between Article 13 and other substantive Convention rights, particularly Articles 2, 3, 5, 6 and 8, highlighting the overlap, absorption, and the lex specialis/lex generali relationship in the ECtHR’s approach. The paper furthermore explores the proceduralisation of Convention rights and the absence of the Court’s clear methodology for examining Article 13 complaints. The paper concludes by identifying remaining issues, emphasizing the importance of strengthening national remedial systems as a foundation of principle of subsidiarity and effective human rights protection.Keywords: European Convention on Human Rights, Article 13 of the ECHR, effective remedy, arguable claim, European Court of Human Rights, subsidiarity, domestic remedies